Kontrol Kecepatan Motor BLDC dengan PID - Firefly - Santi Triwijaya; Yuli Prasetyo; Trisna Wati (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
Conventional DC motors often experience problems that require regular maintenance. The use of conventional DC motors can be replaced with Brushless DC (BLDC) motors. This BLDC motor has good efficiency and durability. Increasing the ability of BLDC motors can be done by speed regulation using the Proportional-Integral-Derivative (PID) method combined with Firefly Algorithm. Testing this method uses matlab 2014a. The firefly algorithm can obtain parameter values of Kp, Ki, and Kd which are then used as PID input. Because of inaccuracies in determining the value of a constant in PID and can cause the length of time to reach the desired speed. BLDC motor speed regulation with the PID method combined with firefly algorithm can make the BLDC motor reach synchronous faster